Membangun Layanan Publik yang Partisipatif: Studi Kasus SIPRAJA melalui Perspektif New Public Governance - Doverianda, Bryan; Wardiyanto, Bintoro; Setijaningrum, Erna (Dinasti Research, 2025)
SIPRAJA (Sistem Pelayanan Rakyat Sidoarjo), developed by the Sidoarjo district government, emerged as a digital solution designed to simplify bureaucratic processes and increase citizen engagement. This study analyzes SIPRAJA through a New Public Governance (NPG) perspective, emphasizing a collaborative and citizen-centered approach to promoting inclusive and responsive governance. By integrating various stakeholders, including government agencies, private actors, and communities, SIPRAJA reflects NPG principles that prioritize co-creation and shared responsibility. This article begins by discussing challenges in traditional public administration that impede efficient service delivery. It then introduces SIPRAJA as an innovative response and explores its conceptual basis within the NPG theoretical framework. Through qualitative analysis and secondary data, this study highlights the impact of SIPRAJA in reducing administrative burden, increasing transparency, and building trust among stakeholders. However, challenges such as digital literacy gaps and infrastructure limitations were also identified, emphasizing the need for adaptive strategies. Findings show that SIPRAJA significantly contributed to the transformation of Sidoarjo's public services by promoting participatory governance, improving service accessibility and conforming to global standards for e-governance. Recommendations include increasing digital inclusion, strengthening public-private partnerships and adopting continuous monitoring mechanisms to ensure ongoing success. This research contributes to the discourse on public sector innovation by showing how NPG principles can be operationalized through technology-based initiatives such as SIPRAJA.